Evidence of disulfide bond scrambling during production of an antibody-drug conjugate. Issue 8 (17th November 2018) - Liu-Shin, Lily Pei-Yao; Fung, Adam; Malhotra, Arun; Ratnaswamy, Gayathri
ABSTRACT: Antibody-drug conjugates (ADCs) that are formed using thiol-maleimide chemistry are commonly produced by reactions that occur at or above neutral pHs. Alkaline environments can promote disulfide bond scrambling, and may result in the reconfiguration of interchain disulfide bonds in IgG antibodies, particularly in the IgG2 and IgG4 subclasses. IgG2-A and IgG2-B antibodies generated under basic conditions yielded ADCs with comparable average drug-to-antibody ratios and conjugate distributions. In contrast, the antibody disulfide configuration affected the distribution of ADCs generated under acidic conditions. The similarities of the ADCs derived from alkaline reactions were attributed to the scrambling of interchain disulfide bonds during the partial reduction step, where conversion of the IgG2-A isoform to the IgG2-B isoform was favored.